The Motivational Origins of Religious Practices - McNamara, Patrick (Zygon, 2002)
I hypothesize that people engage in religious practices, in part, because such practices activate the frontal lobes. Activation of the frontal lobes is both intrinsically rewarding and necessary for acquisition of many of the behaviors that religions seek to foster, including self-responsibility, impulse and emotion modulation, empathy, moral insight, hope, and optimism. Although direct tests of the hypothesis are as yet nonexistent, there is reasonably strong circumstantial evidence (reviewed herein) for it. Recent brain-imaging studies indicate greater anterior activation values and increased blood flow to frontal sites during prayer and meditation. Regular prayer is positively correlated with better overall mental health. Religiosity is correlated with higher levels of self-monitoring, empathy, and moral insight and other positive behaviors and negatively correlated with depression and impulsive and risky behaviors. Independent data show that self-monitoring, empathy, hope, and moral insight are all selectively associated with intact frontal function, whereas depression, impulsiveness, and drug and alcohol abuse are associated selectively with frontal dysfunction. If religious practices do indeed preferentially activate and stimulate development of the frontal lobes, (a) religious practices should be considered as possible adjuncts for some patients in treatment for mental health disorders, and (b) the frontal lobes (rather than the temporal lobes) should be considered the major brain site that supports the core components of religious experience.